2002
DOI: 10.1093/rfs/15.2.489
|View full text |Cite
|
Sign up to set email alerts
|

Underreaction to Self-Selected News Events: The Case of Stock Splits

Abstract: In the last decade, an emerging body of research looking at self-selected, corporate news events concludes that equity markets appear to underreact. Recent theoretical papers have explored why or how underreaction might occur. However, the notion of underreaction is contentious. Concern has focused on two issues-spurious results from unusual time periods and/or misspecified return benchmarks or methods. In this paper, we revisit the issue of underreaction by focusing on one of the most simple of corporate tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
138
2
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(164 citation statements)
references
References 70 publications
20
138
2
4
Order By: Relevance
“…Yet, financial markets sometimes appear to have difficulty correctly interpreting new information on publicly traded firms. Kang et al (1999), Houge et al (2001), Ikenberry and Ramnath (2002) and Lamont and Thaler (2003) all provide recent evidence of apparent capital market failure to properly price equity shares.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, financial markets sometimes appear to have difficulty correctly interpreting new information on publicly traded firms. Kang et al (1999), Houge et al (2001), Ikenberry and Ramnath (2002) and Lamont and Thaler (2003) all provide recent evidence of apparent capital market failure to properly price equity shares.…”
Section: Introductionmentioning
confidence: 99%
“…Such events include dividend initiations, resumptions, and omissions [1,2]; earnings forecast revisions [3]; stock repurchases [4]; and stock splits [5,6]. The prices continue to drift in the same direction as the announcement date reaction.…”
Section: Corporate and Dividend Events Studiesmentioning
confidence: 99%
“…However, a growing amount of studies show that the activity of financial markets reflected by movements of stock prices does not always comply with the Efficient Market Hypothesis as determined by Fama [6]. While the results of some studies show that stock markets overreact to news [2], [15], [1], the others observed an underreaction [21], [7], [11]. Thus in many cases the role of information in stock markets could not be determined as unambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Bearing in mind the fact that the main source of new information about any company gained by the concerned parties usually are the public announcements which companies deliver in various ways, the stock prices on an efficient market should react directly to all the new information announced by companies [6], [7]. However, a growing amount of studies show that the activity of financial markets reflected by movements of stock prices does not always comply with the Efficient Market Hypothesis as determined by Fama [6].…”
Section: Introductionmentioning
confidence: 99%